Innovation Public Service in Maluku Province - Zainal Abidin Rengifurwarin; Julia Th. Patty (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This research aims to analyse and explain the condition of public service quality, the ability to implement public service innovation strategies, as well as the development of individual employee human resource capacity factors, system/ institutional support factors and community role factors at the Maluku Provincial Revenue Agency (BPDP). The problem faced in this research is formulated: how is the implementation of public service innovation strategies, and what are the supporting determinants and inhibitors of public service innovation at BPDP Maluku? This research is descriptive quantitative, by examining 62 respondents, through the distribution of questionnaires. The data analysis technique is non-parametric statistics, using a 5-point Likers scale. The findings of this research illustrate that variable X: the implementation of public service innovation strategies is in sufficient condition (50%), influenced by variable deteminan factors: the ability of individual employee human resources, system/ institutional support factors, as well as factors of community participation that are not optimal (40%). The implication of these findings is that if you want to improve the quality of public services, you need the ability to implement public service innovation strategies determined by individual employee ability factors, system/ institutional support factors, and community participation factors.